Leaf Wax Lipid Extraction for Archaeological Applications. Issue 3 (13th August 2020) - Patalano, Robert; Zech, Jana; Roberts, Patrick
Abstract: Plant wax lipid molecules, chiefly normal ( n ‐) alkanes and n ‐alkanoic acids, are frequently used as proxies for understanding paleoenvironmental and paleoclimatic change. These are regularly analyzed from marine and lake sediments and even more frequently in archaeological contexts, enabling the reconstruction of past environments in direct association with records of past human behavior. Carbon and hydrogen isotope measurements of these compounds are used to trace plant type and water‐use efficiency, relative paleotemperature, precipitation, evapotranspiration of leaf and soil moisture, and other physiological and ecological parameters. Plant wax lipids have great potential for answering questions related to human‐environment interactions, being for the most part chemically inert and easily recoverable in terrestrial sediments, including those dating back millions of years. The growing use of this technique, and comparison of such data with other paleoenvironmental proxies such as pollen and phytolith analysis and soil carbonate and tooth enamel isotope records, make it essential to establish consistent, best‐practice protocols for extracting n ‐alkanes and n ‐alkanoic acids from archaeological sediments to provide comparable information for interpreting past climatic, ecosystem, and hydrological changes and their interaction with human societies. © 2020 The Authors. Basic Protocol 1 : Total lipid extraction Support Protocol 1 : Weighing the total lipid extract Support Protocol 2 : Cleaning the PSE extraction cells Alternate Protocol 1 : Soxhlet total lipid extraction Alternate Protocol 2 : Ultrasonic total lipid extraction Basic Protocol 2 : Separation of lipids by aminopropyl column chromatography Basic Protocol 3 : Separation of lipids by silver‐nitrate‐infused silica gel column chromatography Support Protocol 3 : Preparation of silica gel infused with 10% silver nitrate Basic Protocol 4 : Methylation of n ‐alkanoic acids Basic Protocol 5 : Gas chromatography mass spectrometry (GC‐MS) Basic Protocol 6 : Gas chromatography isotope ratio mass spectrometry (GC‐IRMS)